2022
DOI: 10.4142/jvs.22182
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and genetic diversity of Feline calicivirus in Moscow metropolitan area

Abstract: Background Feline calicivirus (FCV) is widespread throughout the world. An FCV infection is associated with conjunctivitis, rhinitis, and mouth ulcers that can lead to the animal’s death. Because vaccination is not always effective, it is necessary to monitor the infection regularly. Objectives This study examined the FCV epizootic situation in the Moscow metropolitan area by conducting a molecular phylogenetic analysis of the virus isolates. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Specifically, the expression of angiotensin-converting enzyme 2 (ACE2), which is known as the coronavirus receptor, was detected [ 59 60 ]. The studies on infectious diseases in cats also include the analysis of feline calicivirus (FCV), which is a common viral pathogen in cats and causes respiratory tract disease [ 61 62 ]. RNA-seq studies have revealed that the junctional adhesion molecule-1 gene, which is a cellular binding molecule of the FCV, was not expressed in FCV-infected cats [ 63 64 ].…”
Section: Research Of Other Diseases Via Rna-seqmentioning
confidence: 99%
“…Specifically, the expression of angiotensin-converting enzyme 2 (ACE2), which is known as the coronavirus receptor, was detected [ 59 60 ]. The studies on infectious diseases in cats also include the analysis of feline calicivirus (FCV), which is a common viral pathogen in cats and causes respiratory tract disease [ 61 62 ]. RNA-seq studies have revealed that the junctional adhesion molecule-1 gene, which is a cellular binding molecule of the FCV, was not expressed in FCV-infected cats [ 63 64 ].…”
Section: Research Of Other Diseases Via Rna-seqmentioning
confidence: 99%
“…FCV was first reported in 1957 and has since been isolated in many countries in Asia, America, and Europe [ 2 4 ]. Typical clinical syndromes of FCV infection include upper respiratory tract disease (URTD), oral ulcers, conjunctivitis, rhinitis, fever, diarrhea, and lethargy [ 5 7 ]. Without vaccine protection kittens are more susceptible to severe pneumonia following FCV infection [ 1 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, phylogenetic analysis was performed on VP1 gene [ 10 ]. Considering the genetic diversity of the VP1 gene, FCVs worldwide can be classified into two groups: genogroup I and genogroup II [ 5 , 16 ]. According to previous studies, most FCV strains found in China belong to genogroup II [ 11 ].…”
Section: Introductionmentioning
confidence: 99%